Investigation of Anti-obesity and Anti-hyperlipidemic Activities of Morinda citrifolia Fruits in Rat Model - Hooi-Kheng Beh (Science Faculty of Chiang Mai University, 2019)
Morinda citrifolia L. (Noni) has been used in folk remedies by Polynesians for over 2000 years, and has been used for the treatment of wide variety of diseases. The study was undertaken to evaluate anti-obesity and anti-hyperlipidemic effects of standardized extract and fraction of Morinda citrifolia fruits. Anti-obesity and anti-hyperlipidemic activities of Morinda citrifolia fruits were evaluated using high fat diet induced rats model. The total percentage of body weight increased, body mass index and relative organ weights of the rats were calculated. Blood analysis, hepatic histology and gas chromatography-mass spectrometry analysis also performed in the study. Morinda citrfolia fruits efficiently regulate triglyceride and cholesterol metabolism in high fat diet induced rats. The methanol extract and chloroform fraction of the fruits had significantly lower the percentage of total body weight increased and body mass index of the rats. The study also suggested that the fruits methanol extract and chloroform fraction were able to suppress the development of fatty liver disease. The present findings support the anti-obesity and anti-hyperlipidemic effects of Morinda citrifolia fruits.